Implementation of Subak Functions in Subak Umalayu - Yowana, I Made Adiwidya; Arta, I Nyoman (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
This research aims to examine the implementation of subak functions in Subak Umalayu. The research method used for analysis is qualitative, namely the data and facts found will be described. Next, it will be studied based on existing references or based on logic. The research results show that the implementation of subak functions in Subak Umalayu has gone well. This can be seen from the efforts, activities, innovations and awig-awig in Subak Umalayu which cover the six subak functions, namely (1) religious ceremonial activities, (2) distribution and distribution of irrigation air, (3) operation and maintenance of irrigation networks,, (4) resource mobilization, (5) conflict management, and (6) adoption of innovations related to agricultural development.